Pelatihan Videografi sebagai Media Presentasi Tugas Akhir Mahasiswa Pendidikan Bahasa Indonesia - Ginting, Reza Pahlevi; Mahsa, Masithah; Trisfayani, Trisfayani; Safriandi, Safriandi; Najla, Rizky Rana Sastika; Maghfirah, Riezka; Shabri, Ismail; Salsabila, Salsabila (Penerbit Widina, Widina Media Utama, 2024)
The